2020
DOI: 10.1007/s10530-020-02389-0
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic alternative male mating strategies in invasive alien round goby (Neogobius melanostomus) of the upper Danube River

Abstract: Male alternative mating strategies are a widespread life history choice, yet they have hardly been assessed in the context of fish invasions. As established proxies for alternative life-history strategies, body length and sexual maturity of Ponto–Caspian round goby (Neogobius melanostomus) from the recently invaded upper Danube River were contrasted and differential trophic niche occupation was assessed. Only about 4% of analyzed gobies qualified as potential sneakers which may be explained by the recent and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…The site with the most serious invasion is HSH (48.0%), followed by DLJ (24.2%), HZ (20.0%), HY (16.7%) and ZQ (16.0%) (Table 2). The introduction of non‐native species occurs frequently in other regions and species (Ashrafzadeh et al ., 2021; Cerwenka et al ., 2021; Jarić et al ., 2019). The genomes of populations of bighead and silver carps in Pearl River are now dominated by genetic material sourced from introduced Yangtze River fishes (Li et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The site with the most serious invasion is HSH (48.0%), followed by DLJ (24.2%), HZ (20.0%), HY (16.7%) and ZQ (16.0%) (Table 2). The introduction of non‐native species occurs frequently in other regions and species (Ashrafzadeh et al ., 2021; Cerwenka et al ., 2021; Jarić et al ., 2019). The genomes of populations of bighead and silver carps in Pearl River are now dominated by genetic material sourced from introduced Yangtze River fishes (Li et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, factors such as differences in sampling habitats, sampling gears, or time in the breeding season could also influence these ratios. For example, minnow traps were used in the current study, and in the Marentette et al (2009) and Bose et al (2018) studies, but electrofishing was employed by Cerwenka et al (2021), whereas Bleeker et al (2017) used a combination of electrofishing and bottom trawls. Differences in gear will result in differences in size distribution of sampled fish (Clement et al, 2014), which in turn likely will impact the estimates of tactic ratios.…”
Section: Discussionmentioning
confidence: 97%
“…For example, minnow traps were used in the current study, and in the Marentette et al (2009) and Bose et al (2018) studies, but electrofishing was employed by Cerwenka et al (2021), whereas Bleeker et al…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most round gobies exhibit site‐fidelity during the reproductive season, with males either guarding nests or following a sneaker tactic, where they enter the nest of a different male while a female spawns and attempt to fertilize eggs without investing in nest‐building themselves (Lynch & Mensinger, 2012; Ray & Corkum, 2001). The proportion of sneaker males in a population can vary widely, with values between 4% (Cerwenka et al, 2020) and 40% (Bleeker et al, 2017) reported in different ecosystems. Outside of the reproductive season, they show higher mobility, or even migration patterns to deeper waters (Behrens et al, 2021; Carlson et al, 2021).…”
Section: Introductionmentioning
confidence: 99%